PENDIDIKAN SPIRITUAL ANAK DI TENGAH TANTANGAN DEKADENSI MORAL - Mega Fitri Situmorang; Melpa Sintauli Hasibuan; Monica Seles Seitumorang; Murni Asri Silaban; Rani Bella Siregar; Damayanti Nababan (Pusat Riset dan Inovasi Nasional, 2022)
The family is a place where God expresses His love through a relationship of mutual love, mutual respect and mutual care among all family members. God in His wisdom has given mankind the best model and way of maturing faith, namely through the role of parents as God's representatives to guide children. Given the many negative influences from the development of modern life, both through technology, culture and a free lifestyle that can undermine and hinder the growth of children's faith, every parent should realize that the task of fostering the spirituality of children is not the full responsibility of the church and teachers. -school teachers, but a joint task between parents and the church. The research method used in collecting data for the formation of this journal uses qualitative research with a descriptive analysis approach. It is called descriptive because it explains and describes carefully to get a clear picture. In the spiritual development of children, the most important thing is how faith grows in a child. In the growth of children's faith, parents play the most important role. Parents instill the attitude of a child who grows in the Christian faith.